Colony social structure and burrow architecture of the Lusitanian pine vole, Microtus lusitanicus (Gerbe, 1879) - Resende, João Nuno Ribeiro (2020)
Tese de mestrado, Biologia da Conservação, Universidade de Lisboa, Faculdade de Ciências, 2019